Dietary fiber source and stage of gestation impact water balance, fecal physicochemical properties, serum electrolytes, and markers of gut motility in sows - Crome, Thomas A.; Vahlenkamp, Kyle D.; Self, Rachel M.; Giesemann, Mark A.; Petry, Amy L. (Frontiers in Animal Science, 2025)
The study aimed to evaluate the impact of carbohydrase supplementation, soluble fiber from sugar beet pulp (SBP; 20%), and insoluble fiber from corn dried distillers grains (DDGS; 20%) on water balance, serum electrolytes, gut motility, and fecal physicochemical properties in gestating sows. Thirty-six sows, with an initial body weight of 186 ± 4.6 kg, balanced by parity, were assigned randomly to a 2×2 factorial arrangement of treatments from day 28 to 109 of gestation. The factors were fiber type (insoluble (IF; 355 g/d) or soluble (SF; 98 g/d)) and enzyme supplementation (Rovabio Advance P10). The feeding level was 2.1 kg per day. Two 8-day metabolism periods occurred during mid- (days 50-59) and late-gestation (days 99-108). Fecal samples for physicochemical property analysis and serum samples were taken on day 1 of each period. Water balance was measured from days 4-7, with a water allowance set at 80 mL/kg of body weight per day. Data were analyzed using a linear mixed model, with parity as a random effect and fiber, enzyme, period, and their interactions as fixed effects. Daily water allowance was used as a covariate when necessary. Urine output increased by 22.3% in sows fed IF compared to SF, and by 30.5% from mid- to late-gestation (Fiber, Period P<0.05). Fecal moisture was 21.8% higher in sows fed SF and increased by 12.3% from mid- to late-gestation (Fiber, Period P<0.05). The SF treatment increased fecal water holding capacity (P<0.001) and fecal water binding capacity by 76.6% (P=0.044). Regardless of diet, fecal water binding capacity increased in late gestation (Period P=0.035). Urine output increased by 30.5% in late gestation (Period P=0.028) and fecal moisture output increased by 12.3% (Period P=0.015). Serum sodium and chloride concentrations were increased in late gestation (P<0.05). Plasma cholecystokinin tended to be 28% greater in sows fed SF (P=0.070), and motilin levels decreased among all groups from mid- to late-gestation (Fiber×Enzyme×Period P=0.006). Circulating 5-Hydroxytryptamine decreased in late gestating sows fed carbohydrases (Period×Enzyme P=0.002), as well as sows fed SF (Fiber P=0.004). These findings suggest a redistribution of water in the gastrointestinal tract of late gestational sows fed SF, altering fecal hydration and gut motility.